If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3xsquared + -7 = 69 Reorder the terms: -7 + 3adeqrsux = 69 Solving -7 + 3adeqrsux = 69 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 3adeqrsux = 69 + 7 Combine like terms: -7 + 7 = 0 0 + 3adeqrsux = 69 + 7 3adeqrsux = 69 + 7 Combine like terms: 69 + 7 = 76 3adeqrsux = 76 Divide each side by '3deqrsux'. a = 25.33333333d-1e-1q-1r-1s-1u-1x-1 Simplifying a = 25.33333333d-1e-1q-1r-1s-1u-1x-1
| kx^2-9x+6=0 | | 4x+6=2(4+x)-2 | | x-8=6x-6 | | 3x=4y+-8 | | 6x^3-22x^2+9x=0 | | e^3x=6*e^3*x | | (x-5)(x^2+5x+25)=0 | | 32-2=64 | | 6(3x-2)+9x= | | 3v^2+v+2=0 | | 3t-24+2t=7-1t | | -28-(-8)=x/9 | | 21+-14x=29+x | | (4+w)(5w-9)=0 | | 4p+2p-3x=x | | -9n+10= | | 3c-24=96 | | 3y-8+5(-5)=3(-5)+10 | | -7-3(-6n+8)=-121 | | y+y+5x-4y+7= | | 7(1-4x)=119 | | e^3x=6xe^3 | | 3y-8+5x=3x+10 | | 90=8/5x | | 7(3+4x)-8x=-99 | | 2.5x-1.7*(5-2x)=3x | | -7(-8x+6)+1=295 | | 5x+2y+3p+4y-p= | | 10=ay+3d | | 3t-24+2t=7-t | | 2+5x-1+5x= | | 5t-8=28 |